KUALITAS PERUMAHAN DI DESA MRANGGEN KECAMATAN SRUMBUNG KABUPATEN MAGELANG - Ragil Kurnianingrum (Universitas Negeri Semarang, 2016)
The aims of this research are: 1) Understanding people’s social and economy condition in MranggenVillage, 2) Measuring housing quality in Mranggen Village, 3) Understanding the relationship people’ssocial and economy condition towards housig quality in Mranggen Village. Data technical analysis usedstatistic descriptive, scoring, independent difference experiment, and crosstab. The result of the research: 1)Kedungsari Orchard and Salamsari Orchard each of them has household’s education rate and household’sincome rate with good criteria. Most of household’s in Orchard Kedungsari graduated Junior High School(40%), while in Orchard Salamsari most of graduated Senior High School (45%). people’s house most ofthem stand on heritable land, 2) Most of household’s houses in Kedungsari Orchard and Salamsari Orchardinclude in good criteria, there are 70% in Orchard Kedungsari and 72,5% in Orchard Salamsari, 3) There isfound a significant relationship between household’s education rate toward household’s income, besidehousehold’s income also has a relationship toward housing quality, but the status of land ownership has norelationship toward housing quality.